The perspective of prosthodontic treatment in adolescent - Nadia Kartikasari; Riddo A. Rudhanton; Charlie S. Prajugo; Aisyah RP. Gofur; Ratri M. Sitalaksmi; Karina Mundiratri (Indonesia Prosthodontic Association, 2025)
Background: Tooth loss among adolescents may impair masticatory function, alter speech articulation, and affect facial aesthetics. Prosthodontic treatment provides essential restorative options for replacing missing teeth. However, despite its importance, a considerable gap remains in the literature regarding adolescents’ perspective toward prosthodontic treatment. Objective: This study aims to evaluate the adolescents’ perspective toward prosthodontic treatment. Methods : A self-administered questionnaire were given to participants. The perspective of prosthodontic treatment was evaluated using three sections: awareness, knowledge, and attitude. The data respondent were collected and categorized into poor, fair and good. The statistical analysis was performed using reliability and validity tests, as well as the Kolmogorov–Smirnov test (P > 0.05).Write your abstract here. Maximum 200 words, single paragraph, in English. Include background, objective, method, result, and conclusion. Result: The adolescents have fair awareness, knowledge, and attitude regarding the prosthodontic treatment. Conclusion: These study showed that adolescents’ fair perspective of prosthodontic is still insufficient, highlighting the need for improved early education.